Achieving Project Success for Construction Professionals to Categorize Significant Project Management Innovations and Expertise - J. Rengamani (International Journal of Supply Chain Management, 2018)
This paper gives valuable data about the viability of Project Management Body of Knowledge (PMBOK) by assessing execution of information practice in the development industry. The overviews are broke down by auxiliary condition displaying to test the connection between PMBOK techniques/tools/skills (TTS) and project achievement (PA). Significance performance investigation (SPI) is introduced to decide the need of PMBOK TTS and the markers that impact PS. The SPI can assist development specialists with implementing viable administrative methodologies, upgrade extend execution, and enhance the effectiveness of the utilization of administration assets, along these lines advancing undertaking achievement. This preliminary review uncovers that development experts can create government information to improve the probability of venture success based on the recognized essential TTS and their apparent execution.